The Effect of Procedural Scaffolding in Problem Based Learning on Student Problem-solving Ability in Momentum and Impulse Material - Rudi Purwanto; Arini Hariyati (Tinta Emas Publisher, 2023)
This study aims to determine the problem-solving abilities of students who are taught using procedural scaffolding in problem based learning on momentum and impulse material. This study used a quasi-experimental design. The population of this study were all class X students of Darul Wustha Jerowaru Vocational School for the 2022/2023 academic year. The sample technique uses a random sampling technique. The number of samples used amounted to 40 students. Data collection techniques using essay tests. Test the hypothesis in this study using the t test. From the results of the hypothesis testing of students' problem-solving abilities on momentum and impulse material, tcount is greater than ttable (3.45> 2.02). Thus, the problem-solving ability of the group of students who were given learning using procedural scaffolding in problem-based learning was higher than that of the group of students who were given discovery learning on momentum and impulse material.